2023
DOI: 10.15326/jcopdf.2022.0332
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk and Serious Cardiopulmonary Events in Moderate-to-Severe COPD: Post Hoc Analysis of the IMPACT Trial

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Posthoc analyses of the IMPACT trial, which included patients with variable cardiovascular risks, revealed that the risk of cardiovascular adverse events is significantly increased during a moderate [hazard ratio: 2.63, 95% confidence interval (95% CI): 2.08-3.32] or severe (hazard ratio: 21.84, 95% CI: 17.71-26.93) ECOPD and that the risk remains higher than baseline for 90 days [23]. This analysis also demonstrated that the risk of death was elevated during a severe ECOPD (hazard ratio, 41.22, 95% CI: 26.49-64.15; P < 0.001) [24]. Similar results were found in an observational study in Denmark of patients with COPD and stable CVD (Fig.…”
Section: Prevalence and Incidencementioning
confidence: 54%
“…Posthoc analyses of the IMPACT trial, which included patients with variable cardiovascular risks, revealed that the risk of cardiovascular adverse events is significantly increased during a moderate [hazard ratio: 2.63, 95% confidence interval (95% CI): 2.08-3.32] or severe (hazard ratio: 21.84, 95% CI: 17.71-26.93) ECOPD and that the risk remains higher than baseline for 90 days [23]. This analysis also demonstrated that the risk of death was elevated during a severe ECOPD (hazard ratio, 41.22, 95% CI: 26.49-64.15; P < 0.001) [24]. Similar results were found in an observational study in Denmark of patients with COPD and stable CVD (Fig.…”
Section: Prevalence and Incidencementioning
confidence: 54%
“…However, the risk increase was found to be more prolonged than previously suggested,14 15 28 as it remained elevated for up to 6 months. The shorter duration of elevated risk identified in the post-hoc analyses of the IMPACT trial28 31 may be explained by the close monitoring of patients included in trials, potentially minimising the risk of adverse events, differences in the study populations (eg, underlying cardiac comorbidity) and trial duration. From a pathophysiological perspective, persistent post-exacerbation inflammation may contribute to elevated systemic inflammation and non-recovery of symptoms following the acute phase of the exacerbation 32.…”
Section: Discussionmentioning
confidence: 99%
“…1). Aufbauend auf die Ergebnisse der IMPACT-und der ETHOS-Studie, die bei ähnlichen Patientenpopulationen die Effekte der Behandlung mit unterschiedlichen LABAund LAMA-und ICS-Präparaten evaluierten, kann auch die Behandlung mit Triple-Therapien bei symptomatischen Patienten, die unter Therapie Exazerbationen entwickeln, einen signifikanten Überlebensvorteil im Vergleich zu LABA und LAMA bedingen [22,23].…”
Section: Therapie Und Auswirkung Auf Die Mortalitätunclassified